Phase diagram calculation and experimental research on Fe–12Cr–B–Al–alloys: Berechnung des Phasendiagramms und experimentelle Untersuchungen der Legierung Fe–12Cr–B–Al. Issue 9 (14th September 2016) - Jiang, J.; Yue, M.; Fu, H.; Yuan, Y.; Li‐Long, Z.; Liang, J.
Abstract : The vertical sections of Fe–12%Cr–B–xAl–C system with different aluminum contents have been calculated by use of Thermo‐Calc software and the influence of aluminum content on the phase regions and the parameters of eutectic point have been analyzed. Fe–12.0%Cr–1.0%B–2.0%Al–0.3%C and Fe–12.0%Cr–1.0%B–4.0%Al–0.3%C alloy were chosen to be studied by experiment. The phase transition temperatures were measured by differential scanning calorimetry and the microstructure and the phase type was detected by scanning electrone microscope‐energy dispersive X‐ray spectroscopy and X‐ray diffraction. The results indicate that calculated phase diagrams agree well with the experimental results and further prove the thermodynamics database of Thermo‐Calc software is reliable and it can be used to help design the alloy composition and heat treatment process.